DIGITAL LITERATURE IN INCREASING LEARNING MOTIVATION IN HIGH CLASS SD NEGERI 01 TELUK BATANG : Jurnal Pendidikan Ismardianto - Ismardianto; Afandi; Indri Astuti (Jurnal Scientia, 2022)
Abstract This research was conducted to determine the extent of digital literacy in learning content, especially on learning media at SDN 01 Teluk Batang. The method used is descriptive qualitative to present an overview of the use of digital media in high grade learning at SDN 01 Teluk Batang. This research was carried out at SDN 01 Teluk Batang. The sample is High class, namely grades 4, 5 and 6 of SD Negeri 01 Teluk Batang. The results of this study indicate that digital literacy in the high-class learning process at SD Negeri 01 Teluk Batang has used digital media in the learning carried out so that students are motivated in learning.